A Case Report on Pasteurella multocida Peritoneal Dialysis-Associated Peritonitis: When Cats Think Medical Equipment Are Toys. (16th December 2019) - Mirzai, Saeid; Rifai, Ahmad Oussama; Tidrick, Aron; Huang, Qitan; Hale, Justin
Abstract : Pasteurella multocida is an aerobic gram-negative coccobacillus usually found in the oral cavities of most healthy cats and dogs as part of their natural oral flora. This zoonotic pathogen can cause a variety of infections in humans through bites, scratches, or licking. Infections range from less severe cases, such as infected animal bites and cellulitis, to more severe cases of pneumonia, septic arthritis, osteomyelitis, sepsis, and meningitis. However, the number of reported cases of peritoneal dialysis-associated peritonitis caused by P. multocida has been limited worldwide. Here, we report the case of a 59-year-old man undergoing continuous cycling peritoneal dialysis who developed P. multocida peritonitis, believed to be secondary to domestic cat exposure to dialysis equipment. Due to the increasing trend of pet ownership, patients maintained on peritoneal dialysis should be educated on the importance of strict hygiene and avoiding pet contact with the dialysis equipment, especially in bag exchange areas. Although the best means of preventing such infections is to avoid having pets at home, the positive psychological effects of pet ownership should also be considered. Thus, patients in such situations should be continuously educated and encouraged to be mindful of the importance of environmental hygiene.